The Methodist church on the Prairies, 1896-1914 - Emery, George Neil, 1941- (McGill-Queen's studies in the history of religion., 2001)
"In The Methodist Church on the Prairies, 1896-1914, George Emery uses quantitative methods and social interpretation to show that the Methodist Church was a cross-class institution with a dynamic evangelical culture, not a middle-class institution whose culture was undergoing secularization. He describes its impressive achievements and shows that they compare favourably with those of the Presbyterians and Anglicans."--Jacket